Oral pathology in clinical dental practice - Marx, Robert E. ([S.l.] : Quintessence Publishing Co, Inc., 2019)
While most dentists do not perform their own histologic testing, all dentists must be able to recognize conditions that may require biopsy or further treatment outside the dentist office. This book does not pretend to be an exhaustive resource on oral pathology; instead, it seeks to provide the practicing clinician with enough information to help identify or at least narrow down the differential for every common lesion or oral manifestation of disease seen in daily practice as well as what to do about them. Organized by type of lesion, mass, or disease, each pathologic entity presented includes the nature of the disease; its predilections, clinical features, radiographic presentation, differential diagnosis, and microscopic features; and the suggested course of action for the dental practitioner as well as the standard treatment regimen. In keeping with the concise nature of the text, all but the rarest disease entities include at least one photograph to illustrate the clinical condition. This book distills the comprehensive information from Dr Marx and Dr Diane Stern's award-winning pathology reference text (Oral and Maxillofacial Pathology: A Rationale for Diagnosis and Treatment, ed 2 [Quintessence, 2012]) into practical guidelines for restorative and general dentists everywhere.
Oral pathology in clinical dental practice -- Contents -- Preface -- Chapter 1: Recognizing Abnormalities and Pathologic Conditions -- Chapter 2: Red and White Lesions -- Chapter 3: Masses Within theSoft Tissues of Oral Mucosa -- Chapter 4: Oral Mucosal, Facial, and Neck Masses -- Chapter 5: Infectious Diseases of the Jaws and OralCavity -- Chapter 6: Radiolucent Lesions -- Chapter 7: Radiopaque and Mixed Radiolucent-Radiopaque Lesions -- Chapter 8: Radiopaque Lesions in Soft Tissue -- Chapter 9: Pigmented Lesionsof Mucosa and Facial Skin -- Chapter 10: Lesions of the Facial Skin and Oral Mucosa -- Chapter 11: Exposed Bone Pathologies -- Chapter 12: Vascular Lesions of Oral Mucosa and Skin -- Recommended Reading.
Includes bibliographical references and index.
Keywords: Mouth -- pathology; Jaw -- pathology; Face -- pathology; Mouth Mucosa -- pathology; Mouth Diseases -- pathology; Jaw Diseases -- pathology